Women in print I : design and identities - Alexiou, Artemis, 1991-; Roberto, Rose (Oxford ; New York : Peter Lang Publishing, 2022)
"Women in Print 1 is a collection of essays in two related volumes which consider the diversity of roles occupied by women in the authorship, design, production, distribution and consumption of printed material from the fifteenth century onwards. Focusing on individuals and their careers, Women in Print 1 looks at the role of women in the design of printed work, or more broadly, design issues related to the business of publishing. While it is known that women participated in the development of printing technology and the printing trades, their impact on printing history either as producers, consumers or distributors has not only been neglected and undervalued in some instances - it has been deliberately obscured. Collectively the chapters in this volume cover, and recover, the lives and work of women in design for printing and publishing from medieval Italy to twentieth-century Europe, and highlights how their contributions brought positive change not only to the allied industries of printing and publishing but also to the wider social and cultural settings of their time"--(Provided by publisher.)
boek